The Effect Of Honey Application On Perineal Wound Healing Among Postpartum Women I - Yusmaniar, Erma; Anggraini, Anggraini; Rachmawati, Fijri; Mariza, Ana (JKM (Jurnal Kebidanan Malahayati), 2025)
Background: Perineal tears after childbirth are common and can cause pain, dyspareunia, psychological trauma, and a risk of incontinence, all of which impact the mother’s quality of life. Approximately 85% of women who give birth vaginally experience perineal trauma, with 32–33% due to episiotomy and 52% due to spontaneous lacerations. WHO reports that nearly 90% of normal deliveries experience perineal tears. Honey is one of the natural alternatives known to accelerate tissue regeneration and has proven superior in wound healing. This study aims to determine the effect of honey application on perineal wound healing among postpartum women in the working area of Pekurun Community Health Center, North Lampung Regency.Methods: This quantitative study employed a quasi-experimental design with a two-group pretest-posttest approach. The population consisted of 46 postpartum mothers in the working area of Pekurun Community Health Center, and a total of 30 respondents were selected as samples using purposive sampling. They were divided into two groups: 15 in the intervention group and 15 in the control group. Data were collected through observation sheets and analyzed using univariate and bivariate analysis (paired sample t-test).Results: The research results showed that in the intervention group, the mean perineal wound healing score on day 1 was 10.60 and decreased to 0.53 on day 7, while in the control group, the mean score on day 1 was 10.67 and decreased to 1.60 on day 7. There was a significant effect of honey application on perineal wound healing among postpartum women in the working area of Pekurun Community Health Center, North Lampung Regency (p-value = 0.000). It is recommended that postpartum mothers use honey as one of the complementary treatments for perineal wounds by applying 5 ml of honey twice daily.